1991
DOI: 10.3109/00016349109007918
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Complications and Short‐Term Follow‐Up of Infants Born After in Vitro Fertilization and Embryo Transfer (IVF/ET)

Abstract: Two hundred and six pregnancies occurring after in vitro fertilization (IVF) and embryo transfer (ET) during a 7-year period in Göteborg were analysed with respect to pregnancy outcome. The clinical abortion rate was 26%, the rate of ectopic pregnancy was 10%, the rate of ongoing pregnancies beyond 24 weeks was 15%, and the rate of deliveries was 49% (n = 100). The hospital records of 98 women with the 100 deliveries resulting in 131 infants were studied. Multiple pregnancy occurred in 27%, including one quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The translation to Hebrew (Bidel, 1988) used the same procedure described previously, and for middle-school-age children, internal consistency was found to be 35, test-retestreliability was .87, and concurrent validity as assessed by correlation with teachers' reports of aggression was .78 and with parents' reports was 31. It was found, for example, to differentiate between late-adopted and nonadopted children (Zoran, 1996). In the present study, Cronbach's alpha was .8 1.…”
Section: Methodsmentioning
confidence: 86%
“…The translation to Hebrew (Bidel, 1988) used the same procedure described previously, and for middle-school-age children, internal consistency was found to be 35, test-retestreliability was .87, and concurrent validity as assessed by correlation with teachers' reports of aggression was .78 and with parents' reports was 31. It was found, for example, to differentiate between late-adopted and nonadopted children (Zoran, 1996). In the present study, Cronbach's alpha was .8 1.…”
Section: Methodsmentioning
confidence: 86%
“…Wennerholm et al . have reported that 10% of singletons born after IVF and ET were growth restricted 5. Furthermore Tan et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated considerably higher IUGR, SGA, and hypertension rates in patients being pregnant after assisted reproduction. Thus some studies have found hypertension rates between 11 and 14% and SGA rates between 10 and 13% 4, 5. Other authors have reported normal IUGR and hypertension rates in women undergoing assisted reproduction 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether singleton ART-derived pregnancies are also at high risk of prematurity remains controversial. Some authors have reported higher rates of prematurity in singleton ART pregnancies than in spontaneous pregnancies (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), whereas others found no such difference (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%